Achieving Competence Elements of the Prototype Curriculum through Digital Poster of Fantasy Fairy Tales: A Case Study in Elementary School - Sujinah; Lusi Afritrianita Agtha Isnandar; Tining Haryanti; Eko Supriyanto (The Indonesian Institute of Science and Technology Research, 2023)
In this article, we demonstrated the utilization of digital poster media of a fantasy fairy tale in learning activities for Indonesian students. By observations, we have found that the participants had a low ability to understand the material. This research was conducted to validate the usability of digital poster media in learning activities. We have designed a digital poster containing fantasy fairy tale material to satisfy our objective. The mentioned poster is then used to achieve the elements of phase D of the prototype curriculum. We used the study method of the Hannafin and Peck development model with three phases (needs assessment, designing, and development and implementation). We have conducted evaluation and revision stages in all phases on the corresponding poster. Based on the calculation of the two validation aspects (i.e., subject and media experts), we obtained the value of subject experts as 87.5%; and media experts as 89.58%. The average of the two validators was 88.54 %. Therefore, both validators stated that the mentioned poster is valid. Thus, this poster has the potential to be applied and to improve the competence of the viewer element.